Graphene: The Revolutionary Material of the \(21^st\) Century - Ioana Stanciu (New Horizons of Science, Technology and Culture Vol. 1, 2025)
Graphene is a form of carbon that consists of a single layer of atoms arranged in a two-dimensional lattice, in the form of a honeycomb. This two-dimensional structure gives graphene unique properties. Graphite is best known as the fabric from which pencil lead is made, being made up of layers of carbon. Graphene sheets are very stable, and graphene has a very high mechanical strength but is also flexible. In conclusion, graphene is a material with remarkable properties and huge potential to revolutionise many fields of technology and science. However, there are still several obstacles to overcome in terms of its production and large-scale application.